MUSEQuBES: The Kinematics of O vi-bearing Gas in and around Low-redshift Galaxies - Sayak Dutta; Sowgat Muzahid; Joop Schaye; Sebastiano Cantalupo; Hsiao-Wen Chen; Sean Johnson (The Astrophysical Journal)
We present a detailed study of the kinematics of O vi -bearing gas around 60 low-mass (median ${log}_{10}(M_{\star }/M_{\odot })$ = 8.9) galaxies at low redshift (0.1 < z < 0.7) using background quasars (median impact parameter ≈115 kpc) as part of the MUSE Quasar-fields Blind Emitters Survey (MUSEQuBES). We find that the majority of the O vi absorbers detected within the virial radius have line-of-sight velocities smaller than the escape velocities and are thus consistent with being gravitationally bound, irrespective of the halo mass. However, the fraction of such absorbers declines at larger impact parameters. The Doppler b parameter and the velocity width (Δ v _90 ) of the O vi absorbers exhibit large scatter inside the virial radius of the host galaxies, but the scatter declines sharply at impact parameter D ≳ 2 R _vir . For high-mass galaxies ( ${log}_{10}(M_{\star }/M_{\odot })$ > 9), O vi absorption displays a larger kinematic spread, quantified by the pixel-velocity two-point correlation function (TPCF). However, the difference becomes marginal when the pixel velocities are scaled by the galaxies’ circular velocities. We do not find any significant difference between the TPCF of isolated and group galaxies when the stellar mass is controlled for. A significant fraction of groups (4/6) with four or more member galaxies do not show any detectable O vi absorption, likely due to the passive nature of the nearest galaxies.